Prevalence of antibodies to human parvovirus b19 in saudi women of childbearing age in Makkah - Hani O Ghazi (Wolters Kluwer Medknow Publications, 2007)
Objectives: To determine the seroprevalence rate of immunoglobulin G (IgG) and immunoglobulin M (IgM) to parvovirus B19 in pregnant Saudi women in Makkah. Subjects and Methods: Using enzyme-linked immunosorbent assay (ELISA), a total of 1200 serum samples were tested for antibodies to parvovirus B19 known to cause a variety of clinical syndromes in women and newborn infants. Results: Parvovirus B19 IgG antibodies detected in 46.6% and IgM antibodies were found in 2.25% of different age groups. Conclusion: The previous exposure to parvovirus B19 was determined, and 560 (46.6%) of 1200 pregnant Saudi women tested at their first antenatal visit were seropositive for specific IgG. The rate of maternal infection in susceptible pregnancies was 2.25%. These results were in accordance with previous studies performed in other countries.